The life project in high school: Dialoguing about the protagonist student - Sá , Rafaella Coêlho; Carvalho , Antonia Dalva França; Sousa , Jucyelle da Silva; Alcoforado , Joaquim Luis Medeiros (Seven Editora, 2023)
This article discusses the Life Project advocated by the Base Nacional Comum Curricular do Ensino Médio (BNCC) in Brazil, established by the Resolution Conselho Nacional de Educação, CP nº 4, of December 17, 2018, which emphasizes the role of the student in school . It is the result of a qualitative research whose methodology was the bibliographical analysis on the social function of the school and the formation of the student as a protagonist subject. As a theoretical contribution, it was based on Masschelein and Simons (2017), Goulart (2017) and Pasquali (2017), among others, also addressing socio-emotional skills and the role of the teacher in carrying out the Life Project for High School Students. (Brazil, 2018). The results indicate that the highlighted proposal has as a centrality the development of socio-emotional competences within the curriculum in a mandatory way for the new high school in the action that it called Life Project and that mobilizes the responsible school to re-dimension its Pedagogical Political Project and its educational process to, obligatorily, incorporate actions capable of promoting the protagonism and autonomy of students,  for their critical, creative, ethical and supportive exercise in personal and collective life. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-037